Prevention of rhegmatogenous retinal detachment - Chronopoulos, Argyrios; Schutz, James S.; Finger, Robert P. (Survey of ophthalmology, 2025)
Rhegmatogenous retinal detachment (RRD) is a potentially blinding separation of neurosensory retina from retinal pigment epithelium by fluid passing from the vitreous cavity into the subretinal space through one or more retinal breaks, holes or tears. Although most RRDs can be repaired surgically with one operation, some visual loss often results, especially if the macula has been detached, and a small fraction of RRDs require multiple surgeries with significant morbidity, including permanent severe visual loss. Vitrectomy, the most popular RRD surgery, is associated with temporary visual loss and postoperative positioning with limited activity for 1 or 2 weeks; phakic patients usually require cataract surgery within 2 years. Consequently, RRD prevention would be ideal, achieved by early accurate diagnosis of retinal tears and prophylactic outpatient retinopexy, easy, highly successful in sealing retinal breaks and usually uncomplicated. The interval between retinal tears and detachment of the retina is often long enough for laser retinopexy; however, the importance of retinal tear symptoms and prompt evaluation is not well known by the public nor nonophthalmic medical providers, causing a delay that prevents retinopexy and results in surgical repair. New educational programs are needed. Most RRDs are idiopathic but traumatic RRDs also can be avoided by protective eye wear in hazardous sports and occupations and also timely eye examination and retinopexy. Suggestions for improved retinal tear diagnosis are offered.